F-doped CuCo electrode material, preparation method and application of F-doped CuCo electrode material in treatment of nitrate wastewater
By preparing F-doped CuCo transition metal heterojunction electrode material, using molten salt method and electrochemical in-situ reduction method, the problem of difficult to efficiently electrocatalyze nitrate reduction under mild conditions in the prior art, and the effect of efficient ammonia preparation is achieved.
Patent Information
- Application Number
- CN202411717426.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to efficiently electrocatalyze nitrate reduction under mild conditions to prepare ammonia, and traditional metal catalysts such as Rh are relatively rare and expensive.
The two-step method was used to prepare the F-doped CuCo transition metal heterojunction electrode material. First, the transition metal salt was supported by the molten salt method, and then the electrode material was obtained by the electrochemical in-situ reduction method, which was applied to electrocatalytic reduction of nitrate under neutral conditions.
It has achieved efficient preparation of ammonia under low voltage conditions, with ammonia yields as high as 42.83 mg/h·cm2, Faraday efficiency of 99.36%, and the electrode material has good stability and recycling.
Smart Images

Figure CN119530866A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a technical field suitable for electrode material preparation and electrocatalytic application, and in particular to a transition metal heterojunction electrode material. Background Art
[0002] Reactive nitrogen is a key nutrient for crop growth and food production, but excessive input of reactive nitrogen into terrestrial and freshwater ecosystems can cause water pollution (such as nitrates and ammonium) and air pollution (ammonia and nitrogen oxides), as well as global warming and stratospheric ozone depletion (N2O). It is ultimately transported by the atmosphere, deposited, and collected in the aquatic environment in the form of surface runoff. Nitrogen compounds in water bodies are usually in the form of nitrates (NO3 - ), nitrite (NO2 - ) and ammonium ions (NH4 + ) forms; among them, nitrate is the most easily oxidized and stable form of active nitrogen, with high mobility and water solubility, and is easy to store. Nitrate pollution has become a very serious environmental problem, and the treatment of nitrate-containing (nitrate, nitrite) waste is also imminent.
[0003] Ammonia (NH3) is an important industrial chemical, mainly used to make nitrogen fertilizer and compound fertilizer, and also used as biofuel and refrigerant. At present, ammonia is mainly produced by Haber-Bosch technology. The exothermic process is catalyzed by iron-based catalysts at high temperature (400-500℃) and high pressure (10-30MPa). However, this synthesis route requires high temperature and pressure, harsh conditions and high energy consumption.
[0004] The electrocatalytic nitric acid reduction reaction (NO3RR) to produce ammonia at room temperature and pressure has been developing rapidly, despite the high solubility and low dissociation energy (204 kJ mol -1 ), but there are still many difficulties in obtaining high yield and selectivity of ammonia from nitrate electroreduction, such as the high reduction potential and low binding affinity of nitrate. The reduction of nitric acid requires the effective injection of electrons from the metal site into the lowest unoccupied molecular orbital (LUMO) of nitrate. Therefore, the activity and selectivity of nitrate reduction are limited by the bonding ability of the intermediates on the metal. Among the traditional metal catalysts (Co, Cu, Rh, Pd, Pt, Ag Au and Fe), Rh (rhodium) is expected to have the highest electrocatalytic activity at positive potentials (0-0.4V) due to its moderate nitrate and hydrogen adsorption energy. However, due to the rarity of Rh and its low content in nature, it is expensive and limits its application.
[0005] Therefore, it is necessary to develop new catalytic materials that can electrocatalyze the reduction of nitrates to produce ammonia under mild conditions while avoiding the use of rare precious metals. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the present invention utilizes a two-step method to realize the preparation of metal electrode materials under mild conditions. First, the transition metal salt is loaded on the base electrode by a molten salt method, and then the transition metal alloy electrode material is obtained by an electrochemical in-situ reduction method and applied to the electrocatalytic reduction of nitrate to prepare ammonia under neutral conditions. The whole process does not require large-scale special equipment, the reaction conditions are mild, and it is easy to realize industrial production.
[0007] The purpose of the present invention is to provide a F-doped CuCo transition metal heterojunction electrode material and a preparation method and application thereof.
[0008] The first object of the present invention is to provide a F-doped CuCo heterojunction electrode material, wherein the F-doped CuCo heterojunction electrode material exhibits the characteristics of uniform interlacing of nanorods and nanowires; wherein Cu is in the shape of nanosheets and Co is in the shape of nanowires;
[0009] The Co loading amount in the CuCo heterojunction electrode material is 7.7%-22.9%, the Cu loading amount is 65.6%-53.3%, and the F doping amount is 0.2%-0.6%.
[0010] In a preferred embodiment, the Co loading amount in the CuCo heterojunction electrode material is 7.7%, the Cu loading amount is 65.6%, and the F doping amount is 0.2%.
[0011] In some embodiments, the material is designed to achieve low-energy electrocatalytic ammonia production while achieving high yield and Ferrari efficiency.
[0012] The second object of the present invention is a method for preparing the F-doped CuCo heterojunction electrode material, comprising the following steps:
[0013] S1. Provide a conductive substrate, heat the copper salt to a molten state, immerse the conductive substrate in the molten salt, and obtain a precursor material after the reaction; S2. React the precursor obtained in step S1 with a cobalt source, fluoride, and urea under hydrothermal conditions, and then calcine the hydrothermal product to prepare an F-doped CuCo heterojunction electrode material.
[0014] Furthermore, in step S1, the copper salt is a copper salt having a melting point not exceeding 160°C; preferably at least one of nitrate, chloride, sulfate, phosphate, acetate and carbonate.
[0015] Furthermore, the cobalt source includes but is not limited to nitrate, chloride, sulfate, phosphate, acetate, and carbonate of cobalt.
[0016] Further, the conductive substrate is selected from at least one of titanium foil, stainless steel, foamed copper, foamed nickel, nickel felt, copper felt, and carbon paper;
[0017] The conductive substrate is preferably nickel foam; in some embodiments, a nickel foam with a length of 2 cm and a width of 2 cm is used.
[0018] In some embodiments, the fluoride is at least one of ammonium fluoride, lithium fluoride, sodium fluoride, and potassium fluoride.
[0019] In some embodiments, in step S1, the copper salt is heated to a molten state and then kept at 120-140° C. for reaction; the reaction time is 0.5-3 h; and the reaction time is preferably 0.5-1 h.
[0020] In some embodiments, the molar ratio of the copper salt to the cobalt salt is 0.1 to 3.0;
[0021] In some embodiments, in step S2, the molar ratio of the cobalt salt to the fluoride is 0.5 to 10.0.
[0022] In some embodiments, in step S2, the hydrothermal reaction temperature is 120-200° C., and the reaction time is ≥0.5 h; the hydrothermal reaction pH is 6-7; in some preferred embodiments, the pH is adjusted to 6-7 by urea or ammonia water.
[0023] In some embodiments, the calcination temperature is 200-500° C., and the calcination time is ≥1 h.
[0024] In a preferred embodiment, Cu(NO3)2 is ground evenly and heated to make the metal salt molten, and then the base electrode - nickel foam is placed in the molten salt to react for a period of time; the nickel foam is taken out and cooled to room temperature, and after cleaning and drying, the obtained precursor is placed in cobalt salt and fluoride in different proportions, hydrothermally treated, and calcined to obtain a transition metal heterojunction electrode material attached to the surface of the base electrode.
[0025] The third object of the present invention is the application of the F-doped CuCo heterojunction electrode material in the treatment of nitric wastewater, the synthesis of pharmaceutical intermediates, the electrocatalytic reduction of organic nitrobenzene and its derivatives to amines, and the field of new energy conversion and devices.
[0026] In some embodiments of the present invention, when the material is used as a cathode catalyst in the treatment of nitrate-containing wastewater, the wastewater includes but is not limited to wastewater containing nitrate and nitrite.
[0027] In some preferred embodiments, the application system is a three-electrode system, using an H-type electrolytic cell, including an anode region, a cathode region, a diaphragm, three electrodes and an electrolyte solution; the three-electrode system includes a working electrode, a counter electrode, and a reference electrode; the F-doped CuCo heterojunction electrode material is arranged at the working electrode; the applied voltage range is -0.2V to -0.6V. After power is applied, nitrate nitrogen is catalytically reduced to ammonia.
[0028] Preferably, the three electrodes are a platinum sheet as a counter electrode, a catalyst as a working electrode and a HgO / Hg reference electrode.
[0029] In some embodiments, the electrolyte is neutral, preferably a potassium phosphate buffer solution, with a concentration of 0.1M to 1.0M.
[0030] Preferably, the electrolyte solution is 0.1 M potassium phosphate buffer solution and 0.1 M sodium nitrate solution, and the applied voltage range is -0.25 to -0.55 V (to the reversible hydrogen electrode).
[0031] In some preferred embodiments, the anode region and the cathode region are separated by a proton exchange membrane.
[0032] The beneficial effects produced by the present invention include at least:
[0033] (1) The present application provides an F-doped CuCo transition metal heterojunction electrode material, which has the characteristics of uniform interlacing of nanorods and nanowires; wherein Cu is in the shape of nanosheets and Co is in the shape of nanowires; and has excellent performance in sewage treatment, preparation of ammonia under low voltage conditions, and new energy fields.
[0034] (2) The present application also provides a method for preparing the above-mentioned electrode material. The method has a simple preparation process, high yield, low environmental pollution, low raw material price, low production cost, and mild conditions, which is conducive to large-scale industrial production.
[0035] (3) The transition metal heterojunction electrode material provided by the present application has broad application prospects in sewage treatment, water electrolysis to produce hydrogen, electro-reduction of nitrate to produce ammonia and related new energy fields, especially in the process of nitrate to produce ammonia at low voltage, it can show excellent ammonia yield, high Faraday efficiency and good stability. Under neutral conditions, at -0.55V, its ammonia yield is as high as 42.83mg / h·cm 2 , Faraday efficiency is 99.36%, and it can be recycled more than 15 times with good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings are used to provide a further understanding of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the present application and do not constitute a limitation on the present application. In the drawings:
[0037] Figure 1 is a powder energy dispersive X-ray diffraction pattern of the F-doped CuO@Co3O4 heterojunction electrode material;
[0038] Figure 2 is a powder X-ray diffraction pattern of the F-doped CuO@Co3O4 heterojunction electrode material;
[0039] Figure 3 is a scanning electron microscope image of the F-doped CuO@Co3O4 heterojunction electrode material;
[0040] Figure 4 This is the XPS spectrum of F-doped CuO@Co3O4 heterojunction electrode material;
[0041] Figure 5 It is an electrocatalytic heterojunction electrode material with a 5mVs -1 The polarization curve of the scanning rate;
[0042] Figure 6 is a polarization curve diagram of different heterojunction electrode materials prepared in Example 2;
[0043] Figure 7 is the polarization curve of the electrode material prepared in Example 3-5;
[0044] Figure 8 The ammonia yield (a) and Faraday efficiency (b) of F-doped CuO@Co3O4 heterojunction electrode material in 0.1M potassium phosphate buffer solution at -0.25 to -0.55V.
[0045] Fig. 9 This is the stability test of F-doped CuO@Co3O4 heterojunction electrode material in -0.55V, 0.1M potassium phosphate buffer solution. DETAILED DESCRIPTION
[0046] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the embodiments of the specification. These embodiments are only used to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional conditions or conditions recommended by the manufacturer.
[0047] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. The present invention is not limited to the specific embodiments disclosed below.
[0048] As a preferred embodiment for preparing nano F-doped-Co Cu heterojunction catalyst electrode material, the typical method is as follows: the raw material Cu(NO3)2·3H2O is ground evenly with an agate mortar, and then the ground nitrate is placed in a polytetrafluoroethylene liner and placed in a 140°C oven for 3 hours, and then a 2×2 cm 2 The nickel foam electrode was placed in a polytetrafluoroethylene liner containing molten salt, and after 30 minutes of reaction, it was taken out and cooled to room temperature to obtain an electrode containing transition metal salt materials; Co(NO3)2·3H2O, NH4F, and CH4N2O were added to deionized water and stirred evenly, and a piece of prepared Cu(NO3)2·3H2O precursor was placed in a polytetrafluoroethylene liner, heated to 120°C and maintained for 12 hours. The obtained precursor was then rinsed and vacuum dried, and finally calcined in a tubular furnace to obtain the final product F-doped-CuO@Co3O4 / NF, which was collected after natural cooling.
[0049] The prepared transition metal heterojunction electrode was used as a working electrode to test the application of the obtained heterojunction electrode to the electrocatalytic reduction of sodium nitrate aqueous solutions with different concentrations to produce ammonia. In the electrolytic cell, 0.1M potassium phosphate buffered aqueous solution was used as the electrolyte and 10-100mM sodium nitrate was used as the electrolyte. In the electrochemical test, the potential range of the linear voltammetric scan was -0.25V to -0.55V, and the scan rate was 5mV / s.
[0050] In order to better explain the present invention and to facilitate the comparison of the technical effects of different reaction systems, transition metal copper salt copper nitrate is selected in the following examples for corresponding illustration. However, it should be noted that these embodiments are only used to illustrate the present application and are not used to limit the scope of the present application. Other transition metal copper salts such as acetates, sulfates, chlorides, phosphates, carbonates, etc. have the same characteristics and principles as the following examples, and therefore belong to the protection scope of the present invention.
[0051] Example 1 Preparation of transition metal alloy electrode materials
[0052] The excess raw material Cu(NO3)2·3H2O was ground evenly with an agate mortar, and then the ground Cu(NO3)2·3H2O was placed in a polytetrafluoroethylene liner and placed in a 140℃ oven for 3h. After that, a 2×2cm 2The nickel foam electrode is placed in a polytetrafluoroethylene liner containing molten salt, taken out after reacting for 30 minutes, and cooled to room temperature to obtain an electrode material precursor containing transition metal salt;
[0053] 2mmol Co(NO3)2·3H2O, 1mmol NH4F, and 10mmol CH4N2O were added to 30mL deionized water and stirred evenly. Then, a piece of prepared Cu(NO3)2·3H2O precursor was placed into a 50mL polytetrafluoroethylene liner and heated to 120℃ for 12h. The obtained precursor was then rinsed and vacuum dried, and finally heated in air at 5℃ min -1 The final product F-doped CuO@Co3O4 / NF was collected after natural cooling and annealing at 350 °C for 3 h.
[0054] Example 2 Preparation of heterojunction electrode materials with different F doping amounts
[0055] Same as Example 1, other conditions remain unchanged. The difference is that the content of NH4F is adjusted to 0.5mmol, 3mmol, 5mmol, and 7mmol respectively; the obtained heterojunction electrode materials are named F-doped CuO@Co3O4-0.5, F-dopedCuO@Co3O4-3, F-doped CuO@Co3O4-5, and F-doped CuO@Co3O4-7 respectively.
[0056] Example 3F Preparation of doped heterojunction electrode material
[0057] Same as Example 1, except that cobalt nitrate is replaced by cobalt chloride, and other conditions remain unchanged.
[0058] Example 4F Preparation of doped heterojunction electrode material
[0059] Same as Example 1, except that ammonium fluoride is replaced by calcium fluoride, and other conditions remain unchanged.
[0060] Example 5F Preparation of doped heterojunction electrode material
[0061] Same as Example 1, except that ammonia water is used instead of urea, and other conditions remain unchanged.
[0062] Characterization of F-doped CuCo heterojunction electrode materials:
[0063] Crystal structure analysis of F-doped CuO@Co3O4 / NF sample:
[0064] like Figure 1 Shown: EDX elemental analysis of F-doped CuO@Co3O4 / NF ( Figure 1a) also confirmed the presence of O, Co and Cu in the prepared materials. The EDX of F-doped CuO@Co3O4 / NF-7 ( Figure 1 b) also contains elements such as O, Cu and Co. By comparing the EDX of the two catalysts F-doped CuO@Co3O4 / NF and F-doped CuO@Co3O4 / NF-7, it was found that the content of Co in F-doped CuO@Co3O4 / NF-7 increased significantly, which once again confirmed the successful synthesis of the catalyst. From 7.7% of Co in F-doped CuO@Co3O4 to 22.9% of Co in F-doped CuO@Co3O4-7; correspondingly, the Cu element accounted for 65.6% to 53.3%. Among them, due to the low content of F and the fact that the interior of the catalyst is not fully reflected in the energy spectrum, the content of F is reflected in XPS.
[0065] Powder X-ray diffraction was carried out on a D8 X-ray powder diffractometer from Bruker, Germany, with a fixed target monochromatic light source of Cu-Kα and a wavelength of The scanning range is 5-50°, and the scanning step is 0.02°. The sample is the electrode material prepared in Example 1, such as Figure 2 shown. Figure 2 The simulation diagram in the middle shows the crystal structure analyzed by single crystal X-ray diffraction. The fitted X-ray diffraction pattern is consistent with Figure 2 The spectrum obtained by X-ray diffraction test after grinding sample 1# into powder was compared with the diffraction pattern of the prepared nitrate electrode material powder by XRD, indicating that the nitrate metal heterojunction catalyst was successfully loaded on the nickel foam electrode, and the alloy electrode material was prepared under mild and environmentally friendly conditions, and the prepared material has a very high purity.
[0066] Morphological characterization of F-doped CuO@Co3O4 / NF samples:
[0067] The morphology of the prepared samples was characterized by SEM. Figure 3 As shown, the prepared transition metal heterojunction material exhibits nanorod and nanosheet structures, and the nanorod and nanosheet structure catalysts are evenly distributed.
[0068] X-ray photoelectron spectroscopy (XPS) of F-doped CuO@Co3O4 / NF material
[0069] Typical XPS spectrum of F-doped-Co Cu heterojunction electrode material is shown in Figure 4 As shown, according to the copper 2p3 / 2XPS graph, the binding energy at 932.0 eV belongs to Cu + / Cu, further confirmed the reduction of copper (II) in nitrate, and the XPS of Co again confirmed the presence of trace Co in F-doped-Co Cu alloy. Among them, the binding energy at 685ev belongs to F1s, of which the atomic proportion is 3%. The XPS energy spectrum further confirmed the successful preparation of F-doped-Co Cu heterojunction electrode material.
[0070] F-doped CuO@Co3O4 / NF heterojunction electrode performance characterization:
[0071] Polarization curve of the heterojunction electrode material prepared in Example 1
[0072] The F-doped-Co Cu heterojunction electrode material prepared in Example 1 was used as the working electrode, and the cleaned Hg / HgO electrode and platinum sheet were used as the reference electrode and counter electrode, respectively. 0.1 M potassium phosphate buffer solution and 0.1 M / 0.05 M sodium nitrate aqueous solution were used as electrolytes. The pH of the solution was controlled at 7.0. The electrochemical workstation was operated at 5 mV·s -1 The LSV polarization curve test was performed at a rate of 100 mV / s. Before the linear sweep voltammetry (LSV) test, 20 cycles were scanned at 100 mV / s to reach a stable state, and then the test was performed at a scan rate of 5 mV / s. According to equation E vs RHE =E vs Hg / HgO +0.095+0.059pH to calculate the potential value, where Evs RHE is the relative reversible hydrogen electrode potential (V), E vs Hg / HgO is the relative Hg / HgO electrode potential (V), which is Figure 5 shown.
[0073] Depend on Figure 5 It can be seen that the prepared F-doped-Co Cu heterojunction electrode has high electrocatalytic activity for aqueous solutions with different nitrate concentrations, and shows a high current density at a lower voltage. Therefore, the prepared heterojunction material can electrocatalytically reduce aqueous sodium nitrate solutions with a wide concentration range, and has a high ammonia yield and a high Faraday efficiency, indicating that the prepared heterojunction material has high selectivity and high yield for the electrocatalytic reduction of nitrate solutions.
[0074] like Figure 6 It can be seen that the electrocatalytic activity of a series of F-doped-Co Cu heterojunction electrode materials with different metal ratios prepared in Example 2 towards aqueous solutions containing nitrates is good, among which F-doped-Co Cu (F-doped-Co Cu-1) shows a high current density at a lower voltage.
[0075] like Figure 7It can be seen that the F-doped-Co Cu heterojunction electrodes prepared in Examples 3-5 have relatively high electrocatalytic activity for aqueous solutions containing nitrates, and the LSV curve current is not greatly affected.
[0076] Example 6 Reaction performance of F-doped-Co Cu heterojunction electrode material in electrocatalytic reduction of nitrate to produce ammonia
[0077] The F-doped-Co Cu heterojunction electrode prepared in Example 1 was used as the working electrode, the mercuric oxide electrode was used as the reference electrode, the platinum sheet was used as the counter electrode, the diaphragm was a Nafion proton exchange membrane, and the electrolyte was a 0.1 M potassium phosphate buffer solution and sodium nitrate. In the electrochemical test, the potential range of the linear voltammetric scan was -0.2 V to -0.55 V, and the scan rate was 5 mV / s.
[0078] The NH3 yield and Faraday efficiency of the sample of Test Example 1 in 0.1 M potassium phosphate buffer solution under different constant potential conditions are as follows: Figure 8 The figure shows the Faraday efficiency of synthetic ammonia, and the bar graph shows the NH3 yield (a) and the Faraday efficiency (b). Figure 8 It can be seen that the F-doped-Co Cu heterojunction electrode material of the present invention has good electrocatalytic performance in synthesizing ammonia and excellent selectivity. At a low voltage of -0.55 V vs. RHE, the yield of ammonia is as high as 42.38 mg / h·cm 2 , the Faraday efficiency (FE) is 99.36%. The prepared electrode material has the advantages of high efficiency, low price and easy recycling in new energy fields such as treating nitrate-containing wastewater and electrocatalytic reduction of nitrate to produce ammonia.
[0079] Stability of F-doped-Co Cu heterojunction electrode material: The F-doped-Co Cu heterojunction electrode material prepared in Example 1 was tested for the recyclability of the sample in Example 1 in a 0.1 M potassium phosphate buffer solution at a voltage of -0.55 V vs. RHE. Fig. 9 As shown, after 15 cycles, the catalyst still maintains excellent nitrate reduction ability and high ammonia yield, indicating the stability and cyclic practicability of the prepared catalyst, which is conducive to its application and promotion in industry.
[0080] The present invention adopts molten salt method and hydrothermal method to prepare a F-doped-Co Cu heterojunction electrode material. First, the precursor material is obtained by molten salt method at mild conditions of 120-160°C, and then the precursor is further subjected to hydrothermal reaction with fluoride and cobalt salt, and calcined to obtain transition metal heterojunction electrode material (F-doped CuO@Co3O4 / NF). The electrode material can be used in the fields of wastewater treatment, electrocatalytic ammonia production, and new energy conversion devices; under neutral conditions, the electrocatalytic nitrate nitrogen shows excellent electrocatalytic activity, and its ammonia yield is as high as 42.83mg / h·cm at -0.55V. 2 , Faraday efficiency 99.36%, and can be recycled for more than 15 times, with good stability. The preparation method is convenient for industrial production and is green and environmentally friendly. No special equipment is required in the entire production process; the preparation process is simple, the yield is high, the environmental pollution is small, the raw material price is low, the production cost is low, and the mild conditions are conducive to large-scale industrial production.
[0081] The above are only several embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, using the above disclosed technical content to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
Claims
1. A F-doped CuCo heterojunction electrode material, characterized in that: The F-doped CuCo heterojunction electrode material exhibits the characteristics of uniform interlacing of nanorods and nanowires; wherein Cu is in the shape of nanosheets and Co is in the shape of nanowires; The Co loading amount in the CuCo heterojunction electrode material is 7.7%-22.9%, the Cu loading amount is 65.6%-53.3%, and the F doping amount is 0.2%-0.6%.
2. The method for preparing the F-doped CuCo heterojunction electrode material according to claim 1, characterized in that: The following steps are involved: S1. providing a conductive substrate, heating the copper salt to a molten state, immersing the conductive substrate in the molten salt, and obtaining a precursor material after the reaction; S2. The precursor prepared in step S1 is reacted with a cobalt source and a fluoride under hydrothermal conditions, and then the hydrothermal product is calcined to prepare a F-doped CuCo heterojunction electrode material.
3. The method for preparing the F-doped CuCo heterojunction electrode material according to claim 2, characterized in that: In step S1, the copper salt is a copper salt having a melting point lower than 160° C.; preferably at least one of nitrate, chloride, sulfate, phosphate, acetate, and carbonate; The cobalt source includes, but is not limited to, nitrate, chloride, sulfate, phosphate, acetate, and carbonate of cobalt.
4. The method for preparing the F-doped CuCo heterojunction electrode material according to claim 2, characterized in that: The conductive substrate is selected from at least one of titanium foil, stainless steel, foam copper, foam nickel, nickel felt, copper felt, and carbon paper; And / or, the fluoride is at least one of ammonium fluoride, lithium fluoride, sodium fluoride and potassium fluoride.
5. The method for preparing the F-doped CuCo heterojunction electrode material according to claim 2, characterized in that: In step S1, the copper salt is heated to a molten state and then kept at 120-140° C. for reaction; the reaction time is 0.5-1 h.
6. The method for preparing the F-doped CuCo heterojunction electrode material according to claim 2, characterized in that: In step S2, the molar ratio of the cobalt salt to the fluoride is 0.5 to 10.
0.
7. The method for preparing the F-doped CuCo heterojunction electrode material according to claim 2, characterized in that: In step S2, the hydrothermal reaction temperature is 120-200°C, the reaction time is ≥0.5h, and the hydrothermal reaction pH is 6-7; And / or, the calcination temperature is 200-500° C., and the calcination time is ≥1h.
8. Use of the F-doped CuCo heterojunction electrode material according to any one of claims 1 to 7, characterized in that: It is used in the treatment of nitrate-containing wastewater, the synthesis of pharmaceutical intermediates, the electrocatalytic reduction of organic nitrobenzene and its derivatives to amines, and the conversion of new energy and devices.
9. The use of the F-doped CuCo heterojunction electrode material according to claim 8, characterized in that: When the material is used as a cathode catalyst in treating nitrate-containing wastewater, the wastewater includes but is not limited to wastewater containing nitrate and nitrite.
10. The use of the F-doped CuCo heterojunction electrode material according to claim 9, characterized in that: The application system is a three-electrode system, using an H-type electrolytic cell, including an anode area, a cathode area, a diaphragm, three electrodes and an electrolyte solution; the three-electrode system includes a working electrode, a counter electrode, and a reference electrode; the F-doped CuCo heterojunction electrode material is arranged at the working electrode; and the applied voltage range is -0.2V to -0.6V.
Citation Information
Cited By
Non-noble metal-based bifunctional catalyst with high catalytic efficiency as well as preparation method and application thereof
CN121945133A
Highly catalytically efficient non-noble metal-based bifunctional catalysts, methods of making and using the same
CN121945133B